Protein Interactions in Rhodopseudomonas palustris TIE-1 Reveal the Molecular Basis for Resilient Photoferrotrophic Iron Oxidation - Trindade, Inês B. (2023)
Funding Information: Financial support was provided by the European EC Horizon2020 TIMB3 (Project 810856) and the European Union’s Horizon 2020 research and innovation program under the Marie Skłodowska Curie ITN ConCO2rde (grant agreement No 955740), as well as the COST Action CA21115 Iron–sulphur (FeS) clusters: from chemistry to immunology (FeSImmChemNet). This work was funded by national funds through FC—Fundação para a Ciência e a Tecnologia, I.P. (FCT), Project MOSTMICRO-ITQB with refs UIDB/04612/2020 and UIDP/04612/2020, and the LS4FUTURE Associated Laboratory (LA/P/0087/2020). The N-terminal sequencing service was provided by the ITQB Research facilities. The NMR data were acquired at CERMAX, ITQB-NOVA, Oeiras, Portugal, with equipment funded by the FCT, project AAC 01/SAICT/2016. The IBT was financially supported by national funds through the FCT PT-NMR PhD Program via PD/BD/135187/2017. This work benefited of the support and the use of resources of Instruct-ERIC, specifically the CERM/CIRMMP Italy Centre (PID 4509). Publisher Copyright: © 2023 by the authors.